2009
DOI: 10.4028/www.scientific.net/ddf.289-292.377
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Titanium and Nickel in B2 NiTi

Abstract: Diffusion of both titanium and nickel was measured in the near stoichiometric Ni-49.4at.%Ti alloy with the B2 ordered structure. The radiotracer technique and the 44Ti and 63Ni isotopes were applied in the temperature interval from 900 to 1300 K. The penetration profiles were determined by precision parallel grinding or by ion beam sputtering at larger and smaller penetration depths, respectively. Titanium and nickel diffusivities were found to follow linear Arrhenius dependencies with the pre-exponential fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…If the diffusion mechanism could be considered as vacancy mediated, then we have: E D =E v + E m = 0.78eV+0.7eV=1.48 eV, which is practically coincides with E D determined by radio-tracer method [1,2,31]. According to diffusion data the most probable atom jump is the next-nearest-neighbour jump [32]. Experiments in quasielastic neutron scattering [33] showed that elementary diffusion in B2 compounds occurs via nearest neighbour jumps of atoms.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…If the diffusion mechanism could be considered as vacancy mediated, then we have: E D =E v + E m = 0.78eV+0.7eV=1.48 eV, which is practically coincides with E D determined by radio-tracer method [1,2,31]. According to diffusion data the most probable atom jump is the next-nearest-neighbour jump [32]. Experiments in quasielastic neutron scattering [33] showed that elementary diffusion in B2 compounds occurs via nearest neighbour jumps of atoms.…”
mentioning
confidence: 72%
“…This method showed that Ti atoms diffused to one-two order slower than Ni atoms. It was proposed [2] that as Ni atoms are smaller than Ti atoms they could diffuse by interstitial diffusion mechanism, however, this is impossible [32]. Another assumption also [2,31] has been excluded, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This was governed by the higher rate of self-diffusion on the Ti substrate compared to the rate of primary deposition on the nickel substrate, attributed to the higher self-diffusion coefficient of Ti 33 compared to the diffusion coefficient of Ti or Ni in the Ni−Ti alloy. 34 With deposit growth, the local potential gradient gradually reduced. The cathodic process and Ti deposition indicated that Ti electrorefining from the CuTi alloy is highly feasible; however, its anodic processes require investigation.…”
Section: Acs Sustainablementioning
confidence: 99%
“…In plasma sintering diffusion is favored, besides the temperature, by the pulsating current by increasing the density of point defects, by lowering the activation energies needed to displace these defects, as well as by electromigration [17]. Thus, taking into account the higher Ni diffusion coefficient than that of Ti in NiTi [18], as well as the reinforcement particulates high Ni content, it is possible to obtain a Ni -rich NiTi phase.…”
Section: Magnesium Composites Reinforced With Mechanical Alloyed Nickmentioning
confidence: 99%